Proteomics Study of Peripheral Blood Mononuclear Cells (PBMCs) in Autistic Children - Shen, Liming; Feng, Chengyun; Zhang, Kaoyuan; Chen, Youjiao; Gao, Yan; Ke, Junyan; Chen, Xinqian; Lin, Jing; Li, Cuihua; Iqbal, Javed; Zhao, Yuxi; Wang, Weibin (Frontiers in Cellular Neuroscience, 2019)
Autism is one of the most common neurological developmental disorder associated with social isolation and restricted interests in children. The etiology of this disorder is still unknown. There is neither any confirm laboratory test nor any effective therapeutic strategy to diagnose or cure it. To search for biomarkers for early detection and exploration of the disease mechanisms, here, we investigated the protein expression signatures of peripheral blood mononuclear cells (PBMCs) in autistic children compared with healthy controls by using iTRAQ proteomics approach. The results showed a total of 41 proteins as differentially expressed in autistic group as compared to control. These proteins are found associated with metabolic pathways, endoplasmic reticulum (ER) stress and protein folding, endocytosis, immune and inflammatory response, plasma lipoprotein particle organization, and cell adhesion. Among these, 17 proteins (13 up-regulated and 4 down-regulated) are found to be linked with mitochondria. Eight proteins including three already reported proteins in our previous studies were selected to be verified. Five already reported autism associated pro-inflammatory cytokines (IFN-γ, IL-1β, IL-6, IL-12, and TNF-α) were detected in plasma by ELISA analysis. The results were consistent with proteomic results and reports from previous literature. These results proposed that PBMCs from autistic children might be activated, and ER stress, unfolded protein response (UPR), acute-phase response (APR), inflammatory response, and endocytosis may be involved in autism occurrence. These reported proteins may serve as potential biomarkers for early diagnosis of autism. More specifically, simultaneous detection of three proteins (C3, CALR, and SERPINA1) in the plasma and PBMCs could increase the authenticity of detection.